The Effect of Organizational Culture and Work Ethic through Motivation on the Performance Achievements - Zufri, Moh. Saifudin; Tridayanti, Hermien; Suyono, Joko (Universitas Muhammadiyah Gresik, 2024)
his study aims to determine the effect of organizational culture variables and work ethic on employeeperformance through motivation variables. Conducive conditions of organizational culture in whichstandardized regulations have been arranged, then organizational culture will not have an impact onemployee performance through employee motivation. This condition is caused by the motivation ofemployees who tend not to want to provide creative ideas. Work ethic does not have a positive andsignificant effect on employee performance through motivation, this is because the provision ofrecognition and incentives makes employees work more optimally because they feel more motivatedand more valued. The population in this study were all technicians in the work field of the InformationTechnology Security and Infrastructure Division of the Surabaya City Communication and InformationTechnology Office. The data analysis method uses the Partial Least Square Structural EquationModeling (PLS SEM) method. The results showed that work ethic has a significant effect on motivationand performance, but organizational culture has no significant effect on motivation. Organizationalculture and motivation have no significant effect on performance as well as organizational culture andwork ethic through motivational variables have no significant effect on performance. Organizationswith strong bureaucracy and regularity proved the insignificant influence of organizational culture andwork ethic on performance outcomes with the influence of motivation